Future oxide-based resistive flash memories - Wu, Wenze. (2013)
DRAM, the type of memory cell widely used for high density high speed system memory, faces uncertainty in continued scaling for increased density and performance. Amongst emerging alternative technologies, Resistive Random Access Memory (RRAM) with its high speed and ability to scale further downwards presents itself as a possible candidate to replace DRAM. However the current best RRAM samples slightly fall short of the required endurance, and the device's behavior outside laboratory test setups still has many unknowns. This project looks at possible methods to increase to increase an RRAM device's endurance via external parameters, and to determine if an RRAM's behavior is suitable for use as DRAM's replacement.